2021
DOI: 10.1111/jcmm.16677
|View full text |Cite
|
Sign up to set email alerts
|

Metformin protects against insulin resistance induced by high uric acid in cardiomyocytes via AMPK signalling pathways in vitro and in vivo

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Accumulating evidence from clinical observational studies suggests the involvement of asymptomatic hyperuricemia, independent of crystal formation, in hypertension, atherosclerosis, acute and chronic kidney disease, obesity, metabolic syndrome, fatty liver, insulin resistance (IR), and diabetes ( 3 5 ). Our previous studies also confirmed that hyperuricemia induced an IR state in several peripheral tissues ( 6 8 ), including the liver, myocardium, skeletal muscles, and adipose tissue as well as pancreatic β cells ( 9 ), and was a strong risk factor for type 2 diabetes mellitus (T2DM).…”
Section: Introductionsupporting
confidence: 77%
“…Accumulating evidence from clinical observational studies suggests the involvement of asymptomatic hyperuricemia, independent of crystal formation, in hypertension, atherosclerosis, acute and chronic kidney disease, obesity, metabolic syndrome, fatty liver, insulin resistance (IR), and diabetes ( 3 5 ). Our previous studies also confirmed that hyperuricemia induced an IR state in several peripheral tissues ( 6 8 ), including the liver, myocardium, skeletal muscles, and adipose tissue as well as pancreatic β cells ( 9 ), and was a strong risk factor for type 2 diabetes mellitus (T2DM).…”
Section: Introductionsupporting
confidence: 77%
“…It has been observed that the AMPK activation induced by metformin enhanced translocation of membrane GLUT4 and glucose uptake in insulin-resistant cardiomyocytes [ 86 , 87 ]. Moreover, in hypertrophied rat heart metformin intensified the glycolysis by activating the rate-limiting phosphofructokinase 1 (PFK1) [ 88 ].…”
Section: Mechanisms Of Beneficial Impact Of Metformin On Heart Failurementioning
confidence: 99%
“…Diabetes regularly requires the administration of hypoglycemic drugs to maintain appropriate blood glucose levels and to reduce complications. Data from in vitro and in vivo research showed that hypoglycemic drugs can decrease the concentration of serum uric acid ( 41 ). Further study is needed to determine the exact mechanisms of these observations.…”
Section: Discussionmentioning
confidence: 99%